Early Onset, Long Illness Duration, Epilepsy Type, and Polypharmacy Have an Adverse Effect on Psychosocial Outcome in Children with Epilepsy - Valova, Valeria; Kochan, Aleksandra; Werry, Bianca; John, Rainer; Prager, Christine; Schneider, Joanna; Kaindl, Angela M. (Neuropediatrics, 2020)
Epilepsy is often associated with psychosocial comorbidity and this can be more disabling than the seizure activity. Still, these associated conditions are often underdiagnosed and therefore not sufficiently treated. We studied a large pediatric cohort of 371 patients with epilepsy to identify factors associated with negative outcome. We found that patients with early-onset epilepsy, epilepsy of known etiology, and polypharmacy were the most likely to display cognitive impairment. Behavioral problems were particularly prevalent in patients with an epilepsy duration ≥ 5 years. Similarly, early-onset epilepsy, long illness duration, epilepsy of known etiology, and polypharmacy had an adverse effect on school placement and/or social contact. With polypharmacy being the only potentially modifiable factor, it is important to balance between benefits and adverse effects of antiepileptic drugs and consider alternative therapy options in selected patients such as epilepsy surgery, vagal nerve stimulation, and ketogenic diet early-on.
Keywords: pediatric epilepsy; antiepileptic drugs; comorbidity; psychosocial